Cultural Values, Self-Disclosure, and Conflict Tactics as Predictors of Marital Satisfaction Among Singaporean Husbands and Wives. (April 2013) - Quek, Karen Mui-Teng; Fitzpatrick, Jacki
In the present study, we examined the relationship between marital satisfaction and cultural value orientations (e.g., collectivism–individualism), self-disclosure, and conflict tactics (e.g., exit and loyalty) among Singaporean couples. A total of 160 individuals (80 husbands and 80 wives) participated in this study. The results indicated that self-disclosure and exit conflict tactics were strong predictors of couples' marital satisfaction. Collectivism which has a significant association with loyalty conflict tactics impacts husbands' satisfaction. In contrast, neither collectivism nor individualism was related to wives' satisfaction. Implications for future study and clinical practice were discussed.